IMPLEMENTATION OF NARCOTICS SPLITSING BY PUBLIC PROSECUTORS IN THE PROSECUTION PROCESS AS AN EFFORT TO EASE OF EVIDENCE - Herlina Manullang; July Esther (Awang Long Law Review, 2021)
Public Prosecutors often separate criminal case files (splitsing)for indictments with more than one perpetrator for general criminal cases or special crimes such as narcotics crimes. In the case of a criminal act that has been split, the defendants will testify to each other, whose positions are witnesses and defendants. In the implementation of this splitting implementation, it often violates the principles of fast, simple and low-cost justice and the principle of due process of law, but on the one hand this splitting also makes it easier for the Public Prosecutor to prove. The research method is Juridical Empirical, using primary data sources in the form of interviews and secondary data sources from literature, including books and court decisions. In the implementation of splitsing, the authority is fully in the hands of the Public Prosecutor. The separation of case files (splitsing) is not only based on the lack of evidence, but makes it easier for the Public Prosecutor to analyze a case file.